Система корпоративного управления, дискреционная власть менеджмента и инвестиции компаний в НИОКР: эмпирическое исследование на примере Китая - Донг, Джинг; Ю, Минг; ПироговНикита Константинович (Journal of Corporate Finance Research / Корпоративные Финансы | ISSN: 2073-0438, 2010)
In this article we studied the influence of the corporate governance factors on companies’ R&D investment. The independent outside directors, the structure of the institutional shareholders, the discretionary power of managers, the share held by the state, and the share held by the managers, are included. By using the data from the listed companies in China, we statistically tested our hypothesis. According to the results, we found that the discretionary power of the managers has a significant negative correlation with the level of the company’s R&D investment. The more the outside directors in the board, the more the investment in R&D is for companies. The share held by the managers has a positive relation with the R&D investment. But the degree of share concentration and the shares held by the state show no significant correlation with the R&D investment.